Comparison Study on Sonodirect and Sonoalternate Current Electrocoagulation Process for Domestic Wastewater Treatment - Lelisa Regea Mengistu; Zerihun Asmelash Samuel; Chali Dereje Kitila; Abreham Bekele Bayu (International Journal of Analytical Chemistry)
Nowadays, there is a problem related to wastewater handling which is released from different activities. The electrocoagulation method has been a dominant treatment method for wastewater treatment. There are different forms of electrocoagulation methods for wastewater treatment. Nevertheless, there was no comparison made for the removal efficiency of the sonoalternate current (SAC), alternate current (AC), sonodirect current (SDC), and direct current (DC) electrocoagulation process. The efficiency of electrocoagulation methods was compared for their removal of chemical oxygen demand (COD) from Jimma University domestic wastewater. Batch Reactor DC/AC electrocoagulation cell was used to determine the removal efficiency. During the comparison, the response surface methodology (RSM) was used to analyze and optimize the data taken from the laboratory. Besides, ANOVA was used to analyze the interaction effects of different parameters. The removal of COD from domestic wastewater was achieved with DCE, ACE, SDCE, and SACE which were 82.6%, 86.58%, 88.6%, and 92.5%, respectively, under optimal experimental conditions. From the finding, SACE was more successful at removing % COD than the DCE, ACE, and SDCE methods. For DCE and SDCE, the formation of an impermeable oxide layer at the cathode and the occurrence of corrosion at the anode due to oxidation made the COD removal process less efficient compared with SACE processes. From the experimental results it can be concluded that the SACE has the lowest power consumption and higher process efficiency than the other EC methods and can be a promising solution for removing pollutants from domestic wastewater.